A SURVEY OF THE ORIGIN AND PRACTICE OF THE ISLAMIC ARBITRATION SYSTEM IN NORTHERN NIGERIA - Adam, Adam Yusuf; Aminu, Muntaka Yahaya (Tahdzib Al-Akhlaq: Jurnal Pendidikan Islam, 2023)
This paper examines the origin and practice of Islamic arbitration system (Ḥākimiyyah) with particular reference to Northern Nigeria. The work traces the origin of arbitration and its application in all works of life particularly in areas where the Shari’ah system is practice in Northern Nigeria. The paper brings into limelight the history and various practices of Hakimiyyah in Islam. It also analyses Hakimiyyah in Northern Nigeria from the pre-colonial era, the Kanem Bornu empire and Sokoto Caliphate especially the role played by the rulers of the various empires in ensuring the Islamic courts plays it role in the arbitration of dispute and other issues among Muslims and non-Muslims. Secondary data approach was adopted in paper where literary materials relevant to the research were utilise. It was concluded in the paper that the early Islamization of the Hausaland and the manner in which Islam was embraced had led to the quick emergence of strong institutions that made Islam to be the major source of social and cultural identity of the people in the area. Islamic legal system as one of those social institutions, was the bedrock upon which the Hausa Muslim states were established, particularly during the reigns of the defunct Kanem Borno Empire and Sokoto Caliphate. These two Muslim empires had produced the unique legal system the like of which had existed only during the early days of Islam.